Measuring Learning Outcomes: An Effective Strategy for Evaluation in Secondary School Education in Delta State - Voke, Eyetan (dialektika kontemporer, 2025)
This study examined the extent to which learning outcomes are used as a strategy for evaluating students’ academic performance in secondary schools in Delta State, Nigeria, and identified the major challenges faced by educators and administrators in implementing learning outcome-based evaluation. Using a descriptive survey design, data were collected from 180 respondents comprising teachers and school administrators through a structured questionnaire. Descriptive statistics including means and standard deviations were employed to analyze the extent of learning outcomes’ use and challenges encountered, while a chi-square test was conducted to test the significance of learning outcomes’ usage in student evaluation. Findings revealed that learning outcomes are moderately used to guide the design of assessments, identify student strengths and weaknesses, and communicate evaluation criteria, with respondents acknowledging their importance in improving academic performance evaluations. The chi-square test confirmed a significant use of learning outcomes as an evaluative strategy (χ² = 23.876, p = 0.030). However, challenges such as insufficient instructional resources, heavy teacher workloads, inadequate training, and resistance to change were found to impede effective implementation. Notably, limited support and supervision from school administrators were not perceived as significant obstacles. The study recommends increased provision of teaching materials and assessment tools, enhanced professional development for educators, workload management, and change management initiatives to foster positive attitudes toward learning outcome-based evaluation. Sustained administrative support remains essential to ensure effective adoption and practice. Addressing these challenges will improve evaluation quality and ultimately enhance student academic outcomes in Delta State secondary schools.